1996
DOI: 10.1161/01.cir.93.10.1791
|View full text |Cite
|
Sign up to set email alerts
|

Missense Mutation in the Pore Region of HERG Causes Familial Long QT Syndrome

Abstract: We conclude that the Ile593Arg missense mutation in HERG is the cause of LQT in this family because it segregates with disease, its presence was confirmed in three ways, and it is not found in normal individuals. The Ile593Arg mutation may result in a change in potassium selectivity and permeability leading to a loss of HERG function, thereby resulting in LQT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 16 publications
0
32
0
1
Order By: Relevance
“…Naturally occurring mutations in HERG, producing nonfunctional channels and reduced current, underlie the chromosome 7-linked form of long Q-T syndrome (8)(9)(10)(11)(12). Afflicted individuals demonstrate prolonged Q-T intervals and experience sporadic arrhythmias, placing them at risk for sudden cardiac death.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally occurring mutations in HERG, producing nonfunctional channels and reduced current, underlie the chromosome 7-linked form of long Q-T syndrome (8)(9)(10)(11)(12). Afflicted individuals demonstrate prolonged Q-T intervals and experience sporadic arrhythmias, placing them at risk for sudden cardiac death.…”
Section: Introductionmentioning
confidence: 99%
“…Folding defects in this region will lead to channelopathies. For example, mutations in this region cause long QT syndrome and can be fatal (2,3). Folding of Kv channels, as with all proteins, begins as early as the birth of the nascent peptide attached to the ribosome and continues during its tenure in the endoplasmic reticulum (ER) (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…So far, nine mutations or deletions in HERG have been reported in patients with LQT2, including the recent report by Benson and colleagues Schulze-Bahr et al, 1995;Benson et al, 1996). By direct sequencing of HERG, we found a new missense mutation in one Japanese family with LQT…”
Section: Introductionmentioning
confidence: 56%
“…Physiological analysis of HERG have demonstrated that its gene encodes a-subunits that form channels responsible for Ikr, a cardiac delayed rectifier potassium current (Sanguinetti et al, 1995). Benson et al (1996) speculated that mutant HERG subunits may have a so-called dominant negative effect, or some mutations may result in failure of HERG assembly, thereby affecting potassium channel stoichiometry. In either case, conformational change in the amino acid may be critical to the function of HERG, which contributes to the pathophysiological basis for prolongation of repolarization.…”
Section: Discussionmentioning
confidence: 99%